Pengelolaan Aset Pemerintah Dengan Perspektif Pada Kota Administrasi Jakarta Barat Tahun 2021 - Aryanto Aryanto; Tulus Santoso (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aimed to analyze asset management with a Good Governance perspective at the regional asset management office of the administrative city of West Jakarta in 2021. This study used a qualitative method with a descriptive approach. The results of the study indicated that the management of regional property in the West Jakarta Asset Service has several stages in the management. In the implementation of Good Governance, in general, the management fulfilled the principles of Good Governance, i.e.: transparency, participation, accountability, and value of money. The obstacle faced in the process of managing regional property was the supervision of regional assets that was still not contributing to the improvement of effective management. It was because the supervision was not fully routinely carried out and not directly conducted in the field, thus allowing deviation possibilities to the management of regional assets that can cause the loss of regional assets, lightly or heavily damaged goods, and the purchases of goods without bookkeeping. To support the improvement of regional asset management, it is necessary to be followed up with supervision from a direct supervisor (Internal) and functional use (Extern) for preventive and repressive supervision as well as to conduct direct supervision in the field by the supervisory apparatus, so that the possibility of deviations can be relatively smaller and to improve the effective management of regional assets